Revision of the Ambrysus signoreti Stål species complex (Heteroptera: Naucoridae: Ambrysinae). Section 1. - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2022)
The species-rich Ambrysus signoreti Stål species complex is diagnosed and subdivided into three sections based on morphology of the female subgenital plate. The species in the first section, characterized by the posterior margin of the subgenital plate with posterolateral corners extending posteriorly further than the central lobe, are revised. The group includes four species: two previously described from Mexico (Ambrysus cosmius La Rivers, A. schuhi Reynoso & Sites), one from Costa Rica (A. variegatus Usinger), and a new species, A. morelosensis n. sp., from central Mexico. The description of the new species and transfer of A. mormon Montandon to the A. guttatipennis Stål species complex brings the total number of species in the complex to 24 and the total number of described species of Ambrysus to 68. Also, an illustrated key to the species in this first section of the complex is provided. Finally, we present new state records from Mexico for A. cosmius and new province records from Costa Rica for A. variegatus.